Rekayasa Ketangguhan Impak Terhadap Polymer Hybrid Composite Fariasi Penambahan Serat Daun Nanas Dan Serbuk Arang - Harijono, Harijono; Akhmad, Akhmad; Hartono, Hartono (Politeknik Negeri Jember, 2023)
At the moment the demand for materials is increasing with good mechanical properties as well as economical. As an effort to meet these needs, composite materials are used. A composite is a combination of two or more inhomogeneously mixed materials consisting of a matrix and a reinforcement. Various studies conducted generally use one type of fiber so that the composite properties depend on one fiber used. The research that has been carried out has the aim of determining the effect of variations in the addition of pineapple leaf fiber and charcoal powder on the tensile strength and toughness of the impact of polymer hybrid composites. In addition, useful research provides information to readers regarding the strength and toughness of polymer hybrid composite with pineapple leaf fiber reinforcement and charcoal powder.There were three variations in the ratio of pineapple leaf fiber and charcoal powder, namely 10%:30%, 20%:20%, and 30%:10% used in the tensile test. The results showed that the tensile strength increased along with the increase in the volume fraction of pineapple leaf fiber due to good load distribution and the ability to withstand increased tensile load.The average yield of absorbent energy of polymer hybrid composites is 35.81 J, 35.526 J, and 30.93 J, respectively, while the toughness value decreases along with the increase in pineapple leaf fiber due to the bond between the fibers and the matrix that is getting weaker As for the average yield of impact prices of 0.506 J/mm2, 0.466 J/mm2, and 0.39 J/mm2, respectively Keywords: Composite, Polymer Hybrid Fiber Composite, impact, Matrix.